ANALISIS PERBANDINGAN PENDAPATAN PEDAGANG IKAN LAUT KELILING DAN PEDAGANG IKAN LAUT MENETAP DI KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Noviana Rahman; Helminuddin; Nurul Ovia Oktawati (2339-1324, 2020)
This study aims to determine the amount of income of fish pitchmen and fishmongers in Kecamatan Anggana, Kabupaten Kutai Kartanegara. When the research took place for 10 months, the sampling method used was the Census and Disproportionate stratified random sampling method with a sample size of 14 respondents Primary Observation Data (2019). The results showthat the income of fishmongers in Kecamatan Anggana is Rp. 41.967.168,80/month and for the average among per respondent is Rp. 5.993.309,83/month. As for the fish pitchmen is Rp. 22.320.600,20/month with average per respondent is Rp. 3.188.657,17/month. The comparison of income from both sellers shows that the income of fishmonger is bigger than the income of fish pitchman in Kecamatan Anggana. The result of fishmonger’s income is Rp. 5.995.309,83/month while the income of fish pitchman is Rp. 3.188.657/month. The difference in both income is Rp. 2.806.652,66/month.